Revitalizing Education Quality and Services: A Closer Look at Islamic Religious School Committee Strategies - Supriatna, Ucup; Tukiyo, Tukiyo; Sulha, Sulha; Elihami, Elihami; Musthan, Zulkifli (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examined the utilization of school-based management (SBM) principles to enhance the quality of Madrasah Tsanawiyah (MTs) and the implementation of the school-based management concept to improve the quality of MTs. Its purpose is to This study employs a qualitative research methodology utilizing a case study approach. The data collection process involved the utilization of observational techniques, interviews, and films. The acquired data is evaluated using data reduction techniques and then displayed in tables to establish themes that are connected to the current theoretical frameworks. Furthermore, the autonomy of MTs in terms of meeting facilities and the availability of infrastructure is commendable. Subsequently, MTs engaged in collaboration with a diverse range of domestic and international players. Furthermore, the participation of stakeholders in school administration is apparent in the provision of funds, facilities, and support for the implementation of the work program at MTs. The madrasah demonstrates transparency by its open communication of information via congregational activities, MTs bulletin boards, and websites. This study suggests that school leaders should familiarize all stakeholders with the concept of school-based management in order to ensure that they all have a strong sense of responsibility for their particular jobs, with the goal of enhancing the quality of education.